The Role of Social and Cultural Values in Public Education in Remote Island: a Case Study in Karimunjawa Islands, Indonesia (Universitas Negeri Semarang, 2015)
This paper aims to analyze education problems in remote islands especially in Parang island of Karimunjawa Islands, Indonesia. Specifically, this paper aims to identify socio-cultural values and its role in education both formal and nonformal. The research was conducted in the Parang Island one of thousand remote islands in Indonesia. The result shows that education in Parang island encounter strategic issues including the teacher attendance who mostly comes from outside of the island. Their mobility of certain matters force the teachers to go out from the island but sometime because of geographical condition their return to the island is unable to be ensured. This natural constraints precisely construct typical socio-cultural values especially in local education. The values which include multiculturalism, mutual cooperation, and togetherness has integrated into some subjects such as, Citizenship Education, Indonesian Language, Islamic Education, and some local contents such as Marine Education. It has been internalized into empirical experiences of the students as part of marine community that is typically open and egalitarian in character. Meanwhile, Islamic tend to be patterned in syncretism which promote balance and harmony of life. These values have been practices transmitted in religious education such as madrasah and some of informal Islamic institutions. The multiculturalism live, in harmony is effectively socialized through education, family life and community.Artikel ini mengkaji permasalahan bagaimana kondisi pendidikan di Pulau Parang sebagai pulau terpencil berlangsung dan bagaimana peranan nilai-nilai sosial budaya di dalamnya. Hasil penelitian menunjukkan bahwa pendidikan di Pulau Parang menghadapi berbagai persoalan strategis antara lain eksistensi guru tetap yang hampir semuanya berasal dari luar pulau dengan mobilitas yang tinggi harus sering ke luar pulau dan karena gelombang laut yang besar sering tidak dapat dipastikan waktu kembalinya ke Pulau Parang. Kendala alamiah ini justru mengkonstruksi nilai-nilai sosial budaya khas Pulau Parang yang berperan penting dalam beragam pendidikan. Nilai multikulturalisme, sambatan, tolong menolong, dan kebersamaan diinternalisasikan secara intensif melalui mata pelajaran IPS, PKN, BI dan PAI yang dintegrasikan dalam pengalaman empirik murid yang multietnik sebagai etnik maritime dengan karakter terbuka dan egaliter. Nilai-nilai religiusitas keIslaman yang cenderung bercorak sinkritisme mengedepankan keseimbangan dan keselarasan hidup ditransmisikan dalam pendidikan Madrasah Diniyah Mathali’ul dan beberapa ‘pondok’ perseorangan. Nilai-nilai multikulturalisme disosialisasikan secara efektif melalui pendidikan, keluarga dan masyarakat.